The Impact of the Collaborative Creativity Learning Supported Google Earth on Students Spatial Thinking Ability - Pratiwi, Visna Shalsa; Purwanto; Prawira, Akvian Erie; Rosidah, Nikmatur; Prayitno, Arif Dio Esa (Future Space: Studies in Geo-Education, 2025)
Collaborative Creativity Learning (CCL) is a learning model that has the advantage of being applied, namely that students can find new ideas by designing, building and experiencing the surrounding environment and students can be directly involved in learning. This research aims to see the effect of the CCL model assisted by Google Earth on students' spatial thinking abilities. The research was conducted at State Senior High School 1 Balung with a quasi-experimental design by applying a posttest control group design. Data collection was obtained from a spatial thinking ability test with questions arranged according to indicators. Analysis of the data obtained using the independent sample t-test showed a significance result of 0.000 or <0.05. The average score for spatial thinking ability in the experimental class was 83, higher than the control class at 73, thus showing that the CCL model assisted by Google Earth had an effect on students' spatial thinking ability. This phenomenon is explained by the fact that the use of this model encourages students to practice their ability to explore ideas related to geographic phenomena problems and encourages students to be actively involved in mastering concepts.